ASSESSING INCOME GENERATION ACTIVITIES IN WEST AND CENTRAL DARFUR STATES - Abdulrahman , Badreldin Mohamed Ahmed; Abdelmalik, Tarig Ibrahim Mohamed (International Journal of Research -GRANTHAALAYAH, 2015)
Income defines as the money that an individual or business receives in exchange for providing a good or service or through investing capital and it is consume to fuel day to day expenditure. This study has been conducted in 2014. The objective of this study is to assess income generation activities in Darfur, particularly in Geneina and Zalingei localities of West and Central Darfur (WCD) by using questionnaire its size 80 individuals, we obtained the following results a. Agriculture is the main and alternative source of income in WCD b. Financing is the main problem in WCD c. The role of National and local government and united nations (UN) agencies in generating income is less than that played by non-governmental organizations (NGOs) and international non-governmental organizations (INGOs).